Regional variation in demography, distribution, foraging, and strategic conservation of lesser prairie-chickens in Kansas and Colorado - Sullins, Daniel S. (Kansas State University, 2017)
The lesser prairie-chicken (Tympanuchus pallidicinctus) is 1 of 3 prairie-grouse species in North America. Prairie-grouse have undergone local or widespread declines due to a loss of habitat through conversion to row crop agriculture, anthropogenic development, and alteration of ecological drivers that maintain quality grasslands. For lesser prairie-chickens, habitat loss and declines were deemed significant for listing as threatened under the Endangered Species Act in 2014. Despite a judge vacating the listing decision in 2015, the lesser prairie-chicken remains a species of concern. Conservation plans are currently being implemented and developed. To maximize the effectiveness of efforts, knowledge of the distribution of lesser prairie-chickens, regional demography, foods used during critical life-stages, and where to prioritize management is needed. To guide future conservation efforts with empirical evidence, I captured, marked with transmitters, and monitored female lesser prairie-chickens in Kansas and Colorado during 2013–2016 (n =307). I used location data to predict the distribution of habitat. Encounter data from individuals were used to estimate vital rates and integrated into a matrix population model to estimate population growth rates (λ). The matrix model was then decomposed to identify life-stages that exert the greatest influence on λ and vital rate contributions to differences in λ among sites. After assessing demography, I examined the diet of adults and chicks during critical brood rearing and winter periods using a fecal DNA metabarcoding approach. Overall, potential habitat appears to compromise ~30% of the presumed lesser prairie-chicken range in Kansas with most habitat in the Mixed-Grass Prairie Ecoregion. Within occupied sites, populations were most sensitive to factors during the first year of life (chick and juvenile survival), however, the persistence of populations through drought may rely on adult survival. Among regional populations, breeding season, nest, and nonbreeding season survival rates contributed most to differences in λ among sites, breeding season survival contributed to differences in λ among more and less fragmented sites. During critical life-stages, diets were comprised of arthropod and plant foods. Among 80 readable fecal samples, 35% of the sequences were likely from Lepidoptera, 26% from Orthoptera, 14% from Araneae, and 13% from Hemiptera. Plant sequences from 137 fecal samples were comprised of genera similar to Ambrosia (27%) Latuca or Taraxacum (10%), Medicago (6%), and Triticum (5%). Among cover types, lesser prairie-chickens using native grasslands consumed a greater diversity of foods. Last, promising conservation options include the conversion of cropland to grassland through the Conservation Reserve Program (CRP) and tree removal in mixed-grass prairie landscapes. Lesser prairie-chickens mostly used CRP during nesting and the nonbreeding season, during drier periods, and in drier portions of their distribution. Strategic CRP sign-up and tree removal could recover >60,000 ha and~100,000 ha of habitat respectively. In summary, conservation that targets management in areas within broad scale habitat constraints predicted will be most beneficial. In areas occupied by lesser prairie-chickens, management that increases brood survival in large grasslands having optimal nesting structure will elicit the strongest influence on population growth and will likely be the most resilient to stochastic drought-related effects.
Keywords: Lesser prairie-chickens; Grouse; Distribution; Demography; Conservation; DNA metabarcoding